PAR-1 is a novel mechano-sensor transducing laminar flow-mediated endothelial signaling. Issue 1 (December 2018) - Kim, Suji; Han, Jung-Hwa; Nam, Dae-Hwan; Kim, Geun-Young; Lim, Jae; Kim, Jae-Ryong; Woo, Chang-Hoon
Abstract Recent studies have indicated that protease-activated receptor-1 (PAR-1) is involved in cytoprotective and anti-inflammatory responses in endothelial cells (ECs). However, the role of PAR-1 in laminar flow-mediated atheroprotective responses remains unknown. Herein, we investigated whether PAR-1 regulates laminar flow-mediated mechanotransduction in ECs. Confocal analysis showed that PAR-1 was internalized into early endosomes in response to laminar flow. In addition, flow cytometry analysis showed that cell surface expression of PAR-1 was reduced by laminar flow, suggesting that PAR-1 was activated in response to laminar flow. Depletion of PAR-1 using human PAR-1 siRNA inhibited unidirectional laminar flow-mediated actin stress fiber formation and cellular alignment as well as atheroprotective gene expressions in HUVECs. Moreover, PAR-1 knockdown inhibited laminar flow-stimulated eNOS phosphorylation, and inhibited the phosphorylations of Src, AMPK, ERK5 and HDAC5. Furthermore, PAR-1 depletion inhibited laminar flow-mediated anti-inflammatory responses as demonstrated by reduced TNFα-induced VCAM-1 expression and by monocyte adhesion to HUVECs, and prevented laminar flow-mediated anti-apoptotic response. An investigation of the role of PAR-1 in vasomotor modulation using mouse aortic rings revealed that acetylcholine-induced vasorelaxation was diminished in PAR-1 deficient mice compared to littermate controls. Taken together, these findings suggest that PAR-1 be viewed as a novel pharmacologic target for the treatment of vascular diseases, including atherosclerosis.